Remote Control and Monitoring of a Pneumatic Workstation Using TwinCAT 3 and Beckhoff PLC - Tič, Vito; Muhič, Alfonz (International Conference Fluid Power 2025: Conference Proceedings, 2025)
For severe traffic accidents, rapid occupant extrication is crucial. Firefighter hydraulic rescue shears, while essential for this task, are hindered by bulky hydraulic hoses which reduce maneuverability. This research investigates powering these tools with compressed air from a firefighter's self-contained breathing apparatus (SCBA) cylinder. The proposed system utilizes a compact, mobile hydraulic power unit driven by this pneumatic source. A hydraulic rescue shears and review of market solutions are reviewed, and a typical cutting loads are defined. A model of a small, mobile hydraulic power unit powered by an SCBA cylinder is proposed and its performance validated via simulation. This study aims to enhance rescue efficiency and ergonomics by potentially eliminating traditional hydraulic hose constraints.